Use of a national collaborative to improve hospital quality in a low-income setting - Linnander, Erika (Int Health, 2016)
BACKGROUND: Quality improvement collaboratives are a widely used mechanism to improve hospital performance in high-income settings, but we lack evidence about their effectiveness in low-income settings. METHODS: We conducted cross-sectional and longitudinal analysis of data from the Ethiopian Hospital Alliance for Quality, a national collaborative sponsored by Ethiopia's Federal Ministry of Health. We identified hospital strategies associated with more positive patient satisfaction using linear regression and assessed changes in patient experience over a 3-year period (2012–2014) using matched t-tests. RESULTS: A total of 68 hospitals (response rate 68/120, 56.7%) were included in cross-sectional analysis. Four practices were significantly associated with more positive patient satisfaction (p<0.05): posting a record of cleaning activity in toilets and in patient wards, distributing leaflets in the local language with each prescription, and sharing ideas about patient experience across the hospital. Among hospitals that had complete data for longitudinal analysis (44/68, 65%), we found a 10% improvement in a 10-point measure of patient satisfaction (7.7 vs 8.4, p<0.01) from the start to the end of the study period. CONCLUSIONS: Quality improvement collaboratives can be useful at scale in low-income settings in sub-Saharan Africa, particularly for hospitals that adopt strategies associated with patient satisfaction.